The preliminary investigation and mineral characterization of the Gold and Copper at Gindai Yasin, Ghizer, Pakistan - Qureshi, Javed Akhter; Ali, Kamran; Murad, Shukoor; Ali, Arif; Khan, Garee; Ali, Mnzoor; Alam, Muhammad (Journal of Himalayan Earth Sciences, 2020)
Gilgit-Baltistan is known for the extraction of placer gold as well as base metals however, no significant work has been done to investigate the host rock. This study is mainly focused on identification of the host rock for metallic minerals of Gindai Yasin, Ghizer district of Gilgit Baltistan, located towards south-west of the Main Karakorum Thrust (MKT), a mega thrust separating Kohistan Island Arc from the Karakoram plate. The Shamaran volcanics consist of heterogeneous basaltic-andesite to andesite and calc-alkaline rock units. Petrographic results indicate that, the rocks of mineralised zone are felsic to mafic in composition, optical analysis showed that these rocks had gone through extrusive hydrothermal alteration. The rocks mostly comprised of metallic minerals include chalcopyrite, malachite, pyrite and azurite. From the geochemical analysis, a significant portion of the sample is basaltic-andesite to andesite in composition, and mineralised zones are mafic to ultramafic. Gold and copper concentrations varies from 2.43–4.76 ppm, and 26800–98600ppm respectively.